Trial of labour or elective repeat caesarean delivery:are women making an informed decision at Kenyatta national hospital? - Phocas Biraboneye S; Omondi Ogutu; Jos van Roosmalen; Samson Wanjala; Kizito Lubano; John Kinuthia (BMC, 2017)
Abstract Background Trial of labour is a safe option for most women after one previous caesarean delivery. However, the proportion of women attempting trial of labour after previous caesarean delivery (TOLAC) has been declining in many countries. In addition, women with prior caesarean delivery appear to know little regarding their mode of delivery and healthcare providers' recommendations. The doctors' preferences exert a strong influence on patient's decision whether or not to pursue TOLAC. In Kenya, it is unclear whether women who opt for trial of labour after caesarean delivery (TOLAC) or elective repeat caesarean delivery (ERCD) do that based on clear understanding of risks and benefits of both modes of delivery. This study aimed at determining whether patients with one previous caesarean delivery make an informed decision on preferred mode of delivery following their interactions with doctors. Methods A cross-sectional descriptive study was carried out on 202 pregnant women with one previous caesarean delivery at Kenyatta National Hospital (KNH) antenatal clinic. Data was collected from both the patients' records and women were interviewed using a structured questionnaire. Results Out of 202 women with mean age of 30.2 years 136 (67.2%) chose Elective Repeat Caesarean Delivery (ERCD), while 66 (32.8%) opted for TOLAC. Only 61/202 (30.6%; 95% C.I: 24.4 to 37.6%) made informed decisions. Few women (65: 32.2%) knew that the chance of successful TOLAC was high (60-80%) and 97 (48%) were not aware of the chances for a successful TOLAC. More than half of the women (109: 53.9%) were unaware of the risk of uterine rupture after one previous delivery and only few patients (64: 31.7%) knew that the risk of uterine rupture in TOLAC is low (< 1%). The majority of the women (112: 55.4%) did not know that the indications for previous caesarean delivery are an important factor in determining the chance of a successful Vaginal Birth after Caesarean Delivery (VBAC). For 47(23.3%) of the women, there was no documented indication for the previous caesarean delivery. The women's mode of delivery was significantly associated with the preference of the counseling doctor (p < 0.001) and their qualification (p = 0.020). Only 23 (11.4%) women signed the consent form for ERCD while none of the women for TOLAC signed any consent form. Conclusions There was an overall lack of information on both modes of delivery while doctor's preferences affected women's decisions. Only just under one third of the women made an informed decision. There is a need to develop clear standard protocols and checklists for information to be disseminated to doctors and all patients with previous caesarean deliveries in subsequent pregnancies in Kenya.